PENGARUH PENDIDIKAN & PELATIHAN, PENGEMBANGAN KARIR DAN KOMPETENSI TERHADAP KEPUASAN KERJA SERTA PENGARUHNYA TERHADAP PRESTASI KERJA KARYAWAN PT. JASA RAHARJA (PERSERO) CABANG RIAU DAN KEPULAUAN RIAU - novriani parta, Dayu indah (Jurnal Tepak Manajemen Bisnis, 2014)
This r esearch held in PT . Jasa Raharja (Perser o) Riau and Kepulauan riau Branches, which is aGovernment-owned company that providing vehicle-accident loss insurance. This research held in order toanalyze the influence of education and training, career development and competency towards job satisfaction,henceforward, the effect of job satisfaction to job performance.Population are consist of 38 employees of Riau branch and 34 employees of Kepulauan Riau branch. Samplingtechnique done by using cencus method of a 72 existing employees. Education & training, career developmentand competency is used as independent variable, while job satisfaction and job performance used as dependentvariable. Data analyzed by using two stage least square analysis by using SPSS 17 for windows.Result of this study shows that both education & training and career development have positive and significantinfluence on employeeâs job satisfaction, while competency shows a negative but not significant effect on jobsatisfaction. Henceforward, employeeâs job satisfaction positive and significantly influence employeeâ s jobperformance.It is recommended to conduct a pr e-analysis of training necessity , a fair and transpar ent career developmentprogram, social competency enhancement, periodically releasing job satisfaction survey and providing aperformance-based remuneration (incentives) system.Keywords: Eduacation & Training, Career Development, Competency, Job Satisfaction and Job Performance